If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -12 = -2x + 2 Reorder the terms: -12 + 3x = -2x + 2 Reorder the terms: -12 + 3x = 2 + -2x Solving -12 + 3x = 2 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -12 + 3x + 2x = 2 + -2x + 2x Combine like terms: 3x + 2x = 5x -12 + 5x = 2 + -2x + 2x Combine like terms: -2x + 2x = 0 -12 + 5x = 2 + 0 -12 + 5x = 2 Add '12' to each side of the equation. -12 + 12 + 5x = 2 + 12 Combine like terms: -12 + 12 = 0 0 + 5x = 2 + 12 5x = 2 + 12 Combine like terms: 2 + 12 = 14 5x = 14 Divide each side by '5'. x = 2.8 Simplifying x = 2.8
| 8-8c-8c-4b-4b= | | 5x-20=-3x+20 | | x-5-7=2(x+2) | | 12(x-3)-32=5(13+x) | | 92+53+115+2x+3x=540 | | 0=7/6x+6 | | 2(-8+6x)=-4 | | 2(5x+7)=-42+26 | | 5(-6x+3)=15 | | 1x-3=-4x+37 | | 1=7/6x+6 | | -1(5x-3)=1 | | 2x+42=-4x | | -5x+6-x=-6 | | 2x-8=-3x+22 | | 6x+7(2-x)=14-9x-8 | | Y=7/6(0)+6 | | 3x-9=-4x+19 | | 1x-4=-4x+36 | | 3(x+5)(x-10)=7 | | 79-17/8 | | 8=-3x+4x+1 | | 3(c-5)+4c(c-5)= | | 11x-7x=4 | | 3(x-4)=2(5x-11) | | 6x-3(1)=0 | | -7x-9=54 | | 4x+48=-2x | | 5x-15=-2x+20 | | 2x-6=-4x+42 | | x=5::3:2.5 | | 6(0)-3y=0 |